On the Measurement of Electric Resistance of Liquid Electrolytes of Accumulator Battery - N. N. Grinchik; K. V. Dobrego; M. A. Chumachenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
Operational control of parameters of electrolytes (first of all–of specific electric conductivity), is an important electrochemical technology. The methods of measurement of electric conductivity of electrolytes is a subject of permanent discussions because of complexity of physical-and-chemical processes accompanying ion transport and of electrolyte polarization near surfaces of electrodes and of electrochemical processes on the electrodes surfaces. Actual highand low-frequency conductometric methods require relatively expensive equipment and are not free of methodological flaws. In this paper a new method of electric resistance of liquid electrolytes is described and substantiated. It is based on automatic performance of a series of measurements of electrolyte resistance at DC, data processing and extrapolation of an appropriate dependence to threshold voltage at measurement cell plates. The character of functions approximating resistance-applied voltage dependence and method of resistance determination are substantiated. The measurements of specific resistance of some electrolytes were performed. The advantages of the proposed method and measuring device are their simplicity, cheapness, reliability and, consequently, wider possibility to utilize it at technological lines and processes, even at such sites of production processes where such a control was impractical earlier. The method can be widely used for express-diagnostics of electrolytes in such areas as electrochemical energy storage, medicine, agriculture, chemical industry, food production.